NAVIGATING RUPEE DEVALUATION: CAUSES, MACROECONOMIC IMPACTS, AND POLICY STRATEGIES FOR FINANCIAL STABILITY IN INDIA (Lex localis - Journal of Local Self-Government, 2025)
Global economic disruptions—particularly the imposition of 50% U.S. tariffs effective August 27, 2025, alongside ongoing geopolitical tensions—have contributed to a sustained depreciation of the Indian rupee, which fell to ₹87.65 per U.S. dollar by August 2025. This study investigates the drivers of this decline and evaluates its broader economic consequences using a combination of empirical econometric models and qualitative policy analysis. Results from a Vector Autoregression (VAR) model indicate that current account deficits (CAD) explain 45% of the variation in rupee depreciation, with each 1% increase in CAD corresponding to a ₹1.8 rise in the USD/INR exchange rate (p < 0.05). Event studies focusing on the 2024–2025 tariff periods reveal a cumulative abnormal return of -0.123%, suggesting a period of market stabilization. Interviews with banking professionals and Q3 2025 data show that a 1% fall in the rupee's value led to a 15% increase in hedging costs and a 0.15% uptick in non-performing assets (NPAs). The paper evaluates measures such as the Reserve Bank of India’s $5 billion market intervention and efforts to expand rupee-based trade settlements. To strengthen financial system resilience, it proposes a policy framework that integrates targeted monetary adjustments—like repo rate fine-tuning—with structural reforms such as export base diversification. These findings offer actionable insights for emerging economies seeking to manage currency pressures in an increasingly protectionist global trade environment.